Callus Induction of Dendrobium discolor Through The Thin Cell Layer (TCL) Technique Added with 2,4-Dichlorophenoxyaceticacid - Iga Permata Hany; Zozy Aneloi Noli; M. Idris (Jurnal Biologi Tropis, 2023)
Thin Cell Layer (TCL) is a plant propagation technique using thin explants (1-2 mm) through tissue culture. Callus induction is a crucial step in establishing plant regeneration. The type and concentration of growth regulators influence callus formation. 2.4 D is a growth regulator that is commonly used for callus induction in various plants. The research aims to determine the effectiveness of thin explants and 2,4-D in inducing Dendrobium discolor callus. The method used a Completely Randomized Design (CRD) with four treatments (1, 2, 3, and 4 mg/L). Adding 1, 2, and 3 mg/L 2,4-D can induce 100% calluses through the TCL explant. The callus has a friable to compact texture. The result showed that 2 mg/L 2,4-D was the best concentration for callus induction of D. discolor through TCL technique, indicating the greenish color, friable texture, and meristematic tissue.